TGF-β2 levels in the aqueous humor are elevated in the second eye of high myopia within two weeks after sequential cataract surgery - Yan, Weijia; Zhang, Yaping; Cao, Junguo; Yan, Hong (Scientific reports, 2022)
Transforming growth factor-β (TGF-β) is the critical regulator of physiological and pathological conditions in lens. The TGF-β signaling pathway is closely associated with high myopia patients. Thirty eyes from fifteen patients with high myopia who received sequential cataract surgery were enrolled in this prospective study. Ten cataract patients with non-myopia were chosen as a control group. Aqueous humor (AH) samples were used to detect the levels of TGF-β1, TGF-β2, and TGF-β3 in both groups. Compared with the non-myopic cataracts patient group, the highly myopic cataracts group had a significantly higher TGF-β2 (P = 0.019). Besides, the level of TGF-β2 of the second eye was significantly higher than that in the first eye in high myopia cataract patients group (P = 0.037). And TGF-β1 showed significant differences with age and axial length of high myopia cataract patients. Therefore, TGF-β2 may contribute to the development of high myopia and cataract surgery increased the expression of TGF-β2.